Comparison of chicken manure rate, planting density and plant support system on growth performance and phytochemical compounds of Gynura procumbens (Lour.) Merr. - Wan Majid, Wan Huda Dinie (2021)
Gynura procumbens is a herbal medicinal plant that has a range of benefits for medical purposes. Traditionally, it is used for the treatment of several diseases inflicting humans and contains high phenolic compounds such as myricetin and kaempferol derivatives. Agronomic practices have been known to affect greatly on the composition of the phytochemical compounds in plants. Hence, this study was conducted to evaluate the effects of different rates of chicken manure, leaf maturity, planting density and requirement of plant support system on growth, physiological characteristics, total dry matter yield and phytochemical compounds of G. procumbens. In Experiment 1, G. procumbens plants was grown with five different rates of chicken manure; 0, 100, 200, 300 and 400 kg ha-1. Harvested leaves were divided into matured and young leaves according to the leaf maturity for phytochemical analyses. Plants receiving 300 and 400 kg ha-1 of chicken manure recorded the highest growth, crop growth rate, leaf area index and total dry matter yield. Total phenolic and total flavonoids content also DPPH activity were significantly affected by the interaction of different rates of chicken manure and leaf maturity. Total phenolic content in mature leaves significantly decreased with increasing rate of chicken manure. Young leaves recorded increased total phenolic content up to the optimum level and decreased with the application of more than 200 kg ha-1 of chicken manure. Total flavonoids content decreased in mature leaves while young leaves recorded the highest total flavonoids content with 100 and 200 kg ha-1. DPPH activity in young leaves from plants treated with 100, 200 and 300 kg ha-1 of chicken manure were high. Kaempferol-3-rutinoside and kaempferol-3-glucoside contents were also significantly affected by the interaction between different application rate of chicken manure and leaf maturity. By increasing the rate of chicken manure, young leaves tended to show a declined trend in both compounds. Considering the effects of chicken manure rate and leaf maturity on growth performance, physiological characteristics, total dry matter production and phytochemical content, 300 kg ha-1 chicken manure rate is selected as the suitable fertilizer rate for cultivation of G. procumbens. Experiment 2 was conducted to determine the suitable planting density of G. procumbens when grown with or without plant support. Plants was grown with two planting densities: 15 plants m-2 and 25 plants m-2 and with and without plant support. Hortonova trellis netting is the type of plant support and has been applied in the second experiment. Plant growth, physiological characteristics, total dry matter yield and phytochemical content were determined based on the selected fertilizer rate (300 kg ha-1) from the first experiment. Planting density of 15 plants m-2 resulted in higher plant growth and total dry matter production per plant. However, leaf area index, crop growth rate and phytochemical content produced were higher on 25 plants m-2 planting density in comparison with 15 plants m-2. Plants grown with and without plant support system on the other hand revealed no significant effect for each of the measured variables. Based on the results from both experiments, optimum growth performance, physiological characteristics, total dry matter production and phytochemical content of G. procumbens could be obtained with an application of 300 kg ha-1 of chicken manure with 25 plants m-2 planting density.